RANCANGAN ALUR PERGERAKAN DALAM VIDEO ANIMASI 3D UNTUK MEDIA VIRTUAL REALITY PROSEDUR VAKSINASI - Rianis Jasper; Yohanes Merci Widiastomo (ULTIMART Jurnal Komunikasi Visual, 2020)
Animations that are presented using virtual reality are important to keep the audience's focus. This is due to the freedom of the audience to direct their views as they wish. The author aims to design the flow of movement in a 3D animated video about the vaccine-rice procedure. So, the audience (kids) will continue to focus on the video. Discussions of movement include the relationship between the concept of personal space and the flow of character movements. In the process of designing a motion, the writer observes references to similar animated films, conducts experiments and literature studies on the principles of animation and the flow of movement.